Design and Simulation of Photovoltaic Modules Performance Improvement Under the Effect of Partial Shading Using MATLAB/Simulink. - Hayder Makkee Namaa (International Journal of Intelligent Systems and Applications in Engineering, 2024)
To discuss the exploitation or investment of solar energy correctly, it is important to take into account the clear and significant influence of the natural conditions of the Earth, in particular (temperature and intensity of solar radiation). The solar cell is the smallest component in the structure of a photovoltaic cell (PV), and it has faced several obstacles from the beginning of solar cell manufacturing until this moment, including manufacturing, design, economic challenges, as well as natural and unnatural. These difficulties include both natural and artificial elements, such as partial shade to which the solar cell or solar cells are exposed within the solar system, which has direct or indirect effects on the process of generating electrical energy from solar cells. Due to the above issues, solar energy cannot be exploited to its full potential or at its best. Through the results of this study, a new approach was discovered, which is to create a completely new solar array by adding a new electronic system connected to the solar structure in order to improve the efficiency of work and production within the solar array. The new system is an electronic system that works to improve the efficiency of the new solar system in producing electrical energy, and this electronic system can be linked to become a crucial component of it. The new solar system works in all lighting conditions, whether normal or abnormal, and under any type of partial shading of the solar cell. Through this new. System, we can see that under normal and abnormal conditions, the electrical energy generated in the new solar system is equivalent to one-third of the energy produced by the previous solar system. In addition, solar radiation tracking uses non-critical techniques or is seen as a catalyst for the solar system after this system, since it is the strategic comparison used to learn more about MPPT technology and different production conditions in low light with an emphasis on the results of shading conditions on solar PV panels, this strategy (MPPT) did not succeed in maintaining productivity, but the proposed model or productive systematic strategy helped sustain the effectiveness of the solar cells or solar energy system. Thus enhancing electric power generation under poor exposure conditions of solar system. The proposed model was chosen because it may be possible to replicate the different non-standard PV frame scales regulated by a new solar system with useful multi-functional applications. The work could provide a new and useful resource in future power generation (PV).